Neanderthals and modern humans : - Finlayson, Clive (Cambridge University Press, 2004)
Neanderthals and Modern Humans, first published in 2004, develops the theme of the close relationship between climate change, ecological change and biogeographical patterns in humans during the Pleistocene. In particular, it challenges the view that Modern Human 'superiority' caused the extinction of the Neanderthals between 40 and 30 thousand years ago. Clive Finlayson shows that to understand human evolution, the spread of humankind across the world and the extinction of archaic populations, we must move away from a purely theoretical evolutionary ecology base and realise the importance of wider biogeographic patterns including the role of tropical and temperate refugia. His proposal is that Neanderthals became extinct because their world changed faster than they could cope with, and that their relationship with the arriving Modern Humans, where they met, was subtle.